2021
DOI: 10.1111/all.15020
|View full text |Cite
|
Sign up to set email alerts
|

Low oxygen levels decrease adaptive immune responses and ameliorate experimental asthma in mice

Abstract: Background: High-altitude therapy has been used as add-on treatment for allergic asthma with considerable success. However, the underlying mechanisms remain unclear. In order to investigate the possible therapeutic effects of high-altitude therapy on allergic asthma, we utilized a new in vivo mouse model. Methods: Mice were treated with house dust mite (HDM) extract over 4 weeks and co-exposed to 10% oxygen (Hyp) or room air for the final 2 weeks. Experimental asthma was assessed by airway hyper-responsiveness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…At short timescales, the impact on the adaptive immune response cut a striking figure. The adaptive immune system relies on B cells and T cells, and in vitro experiments demonstrated that the human adaptive immune response is dependent on the oxygen level [ 23 ]. CX3CR1 is stably expressed on CD8+ T cells [ 24 ], and its expression was highly suppressed on the third day following a quick climb to a high altitude.…”
Section: Discussionmentioning
confidence: 99%
“…At short timescales, the impact on the adaptive immune response cut a striking figure. The adaptive immune system relies on B cells and T cells, and in vitro experiments demonstrated that the human adaptive immune response is dependent on the oxygen level [ 23 ]. CX3CR1 is stably expressed on CD8+ T cells [ 24 ], and its expression was highly suppressed on the third day following a quick climb to a high altitude.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, hypoxia exacerbates asthma through involvement in the renin‐angiotensin system, contributing to epithelial‐to‐mesenchymal transition and airway remodeling 21 . However, contrasting findings suggest that hypoxia can mitigate allergic airway inflammation and improve airway remodeling, yielding beneficial effects on asthma 22–24 . Low oxygen levels induced human umbilical extracellular vesicles from cord mesenchymal stem cells, demonstrating the potential to alleviate allergic airway inflammation and airway remodeling in a chronic asthma mouse model 22 .…”
Section: Introductionmentioning
confidence: 99%
“… 21 However, contrasting findings suggest that hypoxia can mitigate allergic airway inflammation and improve airway remodeling, yielding beneficial effects on asthma. 22 , 23 , 24 Low oxygen levels induced human umbilical extracellular vesicles from cord mesenchymal stem cells, demonstrating the potential to alleviate allergic airway inflammation and airway remodeling in a chronic asthma mouse model. 22 Hypoxia further alleviates allergic asthma by downregulating the MAPK signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Airway mucus hypersecretion is one of the pathophysiological features of asthma. 39 Since clinicians identified mucus plugs as a fatal factor in asthmatic patients in the 1880s, his phenomenon has been continuously and rigorously studied. 24 Consequently, whether airway mucus is effectively cleared is critical for evaluating the effect of asthma treatment.…”
mentioning
confidence: 99%